Free help with homework

Why join Brainly?

  • ask questions about your assignment
  • get answers with explanations
  • find similar questions


Split sin6 nd cos6 into (sin2)3+(cos2)3= use identity a3+b3 = (a+b)(a2+b2-ab) here a=sin2 b=Cos2 put this in identity u will get (sin2+cos2)((sin2)2+(cos2)2-sin2 cos2 )= (1)(sin4+cos4-sin2cos2) then add nd subtract 2sin2cos2= sin4+ cos4 -2sin2cos2+2sin2cos2 - sin2cos2 = (sin2+ cos2)2-3 sin2 cos2= 1-3sin2 cos2
0 0 0
if this is not understood thn u shd go for RD sharma
The Brain
  • The Brain
  • Helper
Not sure about the answer?
Learn more with Brainly!
Having trouble with your homework?
Get free help!
  • 80% of questions are answered in under 10 minutes
  • Answers come with explanations, so that you can learn
  • Answer quality is ensured by our experts